(untitled) (TAMADDUN NURI JURNALI, 2025)
The article uses the novel "Terbenbes" by K. Matmuratov as a source and analyzes the differences in the use of somatic phraseologisms with new oral components. A single mouth plays an important role in the transmission of a person’s inner feelings through his dominant phraseology, his actions.